Some properties of K-Operator Frame in Hilbert $C^{*}$-modules - Eljazzar, Roumaissae; Rossafi, Mohamed; Klilou, Mohammed (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this paper, we present some properties of K-operator Frame in Hilbert $C^{*}$-modules. Topics that will be discussed include: K-operator Frame and Dual K-operator frame in Hilbert $C^{*}$-modules. We will also study K-operator Frame in two Hilbert $C^{*}$-modules with different $C^{*}$-algebras.